The Comparison of Metacognitive Group Intervention and Group Acceptance-Based Behavioral Therapy on Competitive Aggression of Anxious Professional Soccer Athletes in Tehran - Alavizadeh, Seyed Mohammadreza; Sobhi Gharamaleki, Nasser; Entezari, Somaye; Mokhtar, Firdaus (Health Nexus, 2023)
The aim of present study was comparison of metacognitive group intervention and group acceptance based behavioral therapy on competitive aggression of anxious professional soccer players in U-19 league in Tehran. Participants in this study were 60 professional soccer players who were occupied in professional soccer leagues in Tehran. These participants were entered into the assessment stage and after obtaining informed consent, they randomly assigned in one of the three experiment groups MCT MAC, WL. The participants completed the Sport Aggression Styles Inventory in pre-test, post-test and 3 months follow-up stages. The results of present study demonstrate that MCT and MAC can make some changes in aggression styles of anxious soccer players. MCT have been affecting on passive-aggressive and somatic aggression styles. In addition, MAC have been affecting on sadistic and masochistic aggression styles. According to these findings, it would ensure that soccer players affected by anxiety and aggression-related problems get the opportunity to gain advantages from such third wave’s interventions.